Image-Guided Radiotherapy for Prostate Cancer using 3 Different Techniques: Localization Data of 186 Patients. Issue 3 (May 2015) - Garibaldi, Cristina; Jereczek-Fossa, Barbara Alicja; Zerini, Dario; Cambria, Raffaella; Ferrari, Annamaria; Serafini, Flavia; Cattani, Federica; Tagaste, Barbara; Fodor, Cristiana; Luraschi, Rosa; Orecchia, Roberto
Aims and Background: This study evaluates 3 different imaging modalities—ultrasound (US), stereoscopic X-ray imaging of implanted markers (Visicoils) (X-ray), and kV cone-beam computed tomography (CBCT)—to assess interfraction and intrafraction localization error during conformal radiation therapy of prostate cancer. Methods and Study Design: The study population consisted of 186 consecutive prostate cancer patients treated with an image-guided radiotherapy (IGRT) hypofractionated protocol using 3 techniques: 32 with X-ray, 30 with CBCT, and 124 with US. Treatment dose of 70.2 Gy was delivered in 26 fractions with a conformal dynamic arcs technique. Interfraction prostate localization errors were determined for the 3 techniques. Moreover, interfraction and intrafraction prostate motion in terms of translations and rotations, as well as residual errors, were determined with X-ray. Results: The systematic and random components of the prostate localization errors were as follows: (1 ) with X-ray 3.0 ± 3.4, 2.3 ± 2.7, 1.8 ± 2.3 mm in anterior-posterior (AP), superior-inferior (SI), and left-right (LR) directions and 1.8° ± 1.2°, 2.3° ± 1.5°, 2.7° ± 3.1°, for the yaw, roll, and pitch rotations; (2 ) with CBCT3.5 ± 4.2, 3.3 ± 3.3, 2.5 ± 3.1 mm in AP, SI, and LR directions; (3 ) with US 3.7 ± 4.7, 3.4 ± 4.3, 2.3 ± 3.5 mm in AP, SI, and LR directions. Residual errors with X-ray were less than 1 mm in all directions. Intrafraction prostate motion of less than 0.5 mm in LR and of the order of 1 mm in AP and SI directions was found. This led to a significant reduction of the margins, potentially important for dose escalation studies. Conclusions: Daily on-line IGRT with stereoscopic X-ray imaging allowed a consistent PTV margin reduction considering residual interfraction prostate localization error and intrafraction motion. X-ray offers the best compromise among accuracy, reliability, dose to the patient, and time investment for daily IGRT treatment of prostate.